A Discourse Analysis of Canadian PM’s Speech after New Zealand Christchurch Mosque Shootings - Muhammad Amjad (University of Chitral Journal of Linguistics and Literature, 2018)
We use language for different purposes that are mostly related to the social practices in different contexts and perspectives. Discourse analysis is one of the disciplines which examines the use of language from different perspectives to reach a possible understanding of the discourse. This paper is also an attempt to analyze language used in a particular context and perspective to understand and expose some constructed realities. The objective of this study is to examine the Canadian PM’s moral and ideological standpoint, his commitment to show solidarity with the grieved community, his determination to eradicate terrorism and his linguistic characterization of terrorism that he confirmed in his speech in the House of Common on March 18, 2019 after the Christchurch Mosque Shootings in New Zealand. The analysis is based on Fairclough’s conceptions in CDA. It claims that ideologies and texts are interrelated, and it is not possible to break this link between ideologies and texts because the texts can be interpreted in maximum possible ways. This study analyzes the components of ideology and persuasion used in Justin Trudeau’s speech to reveal his commitment and persuasive strategies against terrorism, and it gives new hopes to the targeted communities worldwide as well as the general public. He tried to ensure the public that they are not alone because the world leaders and the heads of the states are unconditionally united to eradicate worldwide terrorism.